CD4 and CD8 T-cell responses to acellular pertussis and rotavirus vaccination in breast-fed HIV exposed, uninfected infants - Nundalall, Trishana (Division of Clinical Immunology, 2017)
Introduction: Vaccination is one of the most efficient ways to prevent infectious diseases, however due to the naivety and regulation of immunity found in infants, induction of vaccine-mediated immunity is challenging. Respiratory and diarrheal diseases are major contributors to infant mortality. Additionally, Human Immunodeficiency Virus-1 (HIV) infections increase the risk of mortality. Current advances in Prevention of Mother-to-Child Transmission (PMTCT) have prevented HIV infections in almost 97% of infants being born to HIV-infected mothers. As a result there is an increasing number of HIV exposed, uninfected infants (HEU). HEU infants have a higher rate of infectious disease related mortality and morbidity compared to unexposed infants, the underling causes of these differences are still not understood. In this dissertation, responses to two childhood vaccines, live, attenuated rotaviral vaccine (Rotarix) and acellular Pertussis (aP), were analyzed in HEU infants, with specific focus on T-cell responses to Rotarix and aP, due to the current lack of published data on T-cell responses. Additionally, the influence of feeding mode, that is breast or formula feeding, was also assessed as it is well established that breast fed infants contract fewer infections compared to formula fed infants. Methods: This dissertation included infants from a larger cohort which includes three groups of infants; HIV unexposed breast fed (UBF), HIV exposed breast-fed (EBF) and HIV exposed formula fed (EFF) infants. Infants were recruited at birth and followed up until 36 weeks of age. As no Rotavirus vaccine T-cell assay was previously published, multiple techniques were utilized to attempt to optimize an assay capable of detecting Rotavirus (RV) vaccine-specific T-cell responses. To determine T-cell responses to Bordertella pertussis (BP), blood was collected from infants at each time-point and 200ul was stimulated with BP antigen in a 12-hour whole blood assay. Cells from all assays were fixed and stained for flow cytometric analysis of CD4 and CD8 T-cell responses. The markers used included live/ dead, CD3, CD4 and CD8 for identification of T-cell populations, IFNγ, IL-2 and TNFα cytokines, HLA-DR and Ki67 for activation and proliferation, and CD45RA and CD27 memory differentiation. Data analysis was then completed using Microsoft Excel, Flow.Jo V9, GraphPad prism V6, Pestle 1.7 and Spice V5.33 software packages. Results: Despite multiple attemps it was not possible to optimise an assay capable of consistently detecting Rotavirus vaccine specific responses. This was partly due to interferance from contaminating agents in the protein antigens used, and difficulty in culturing and purification of whole virus. Assessment of aP spcific CD4+ T-cell memory demonstrated an overall increase in terminally differentiated (TD) memory cells accross time. This mirrored the ontogeny of the total T cell pool which showed an overall decrease in naïve T-cell frequencies with a consequent increase in late and terminally differentiated CD4 and CD8 T-cell populations over time through the first months of life. Both total and aP specific CD4+ early differentiated (ED) memory T-cells remained unchanged over time. ED CD8+ memory T-cells peaked at week 15 in EBF infants. A similar observation was found in UBF infants but at a non-significant level. EFF infants had no significant changes in CD8+ naive, ED and late differentiated (LD) memory populations over time. Additionally all infants demonstrated high levels of Ki67 expression at D4-7, which is prior to vaccination and maintained this level of proliferation after vaccination. HEU infants had higher levels of activation compared to HU infants in the first week of life but this normalised to HU infant levels by week 7. Furthermore EFF infants had peak T-cell activation at week 7 as compared to week 15 in EBF infants. In addition HU infants had better cytokine responses than HEU infants at week 7 but similar responses at week 15 and 36. In Addition, EFF infants also had increased vaccine specific CD4+ responses at week 7 and week 36 compared to EBF infants. This was true for overall cytokine expressing CD4 T-cells and single TNFα expressing CD4+ T-cells. Disscussion: Given the important role T-cells play in the clearance of Rotavirus, it is important that an assay capable of detecting RV vaccine specific T-cell responses be developed. Furthermore, T cells play a role in providing help for antibody responses to BP and for killing of intracellular bacteria. Our findings regarding immunity to aP suggest that all infants, regardless of HIV exposure status and feeding mode, are able to mount a T cell response to aP vaccination. However the differing ontogeny of responses seen in all three groups of infants lends some insight on the complex determinants of vaccine T -cell immunogenicity. In this case, age since vaccination, HIV exposure, and feeding mode resulted in apparent changes in vaccine responses as well as T cell differetiation and activation.